Re-Engineering Client's Remote Display System / Mazlin Shiekh Saleh - Shiekh Saleh, Mazlin (2004)
This system gives a control to lecturer to have power over the student behavior by forcing the student to view the lectures application (for examples the PowerPoint slide presentation) automatically through the student computer without using the Liquid Crystal Display (LCD) screen. Besides that this system also disables the student mouse and keyboard during the lectures hour to get a full attention from the students. By using the Virtual Networking Computing as main core source code, this project is integrated with the other project that manages with the server side. Thus it requires a lot of imderstanding and match ness. However as its title, this report it details about the client side only.